German researchers of Kazakhstan in the 18th – 19th centuries - R.A. Idrisov; O.N. Shirokov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The activity of German researchers studying the territory of Kazakhstan as part of the scientific, diplomatic, and exploratory expeditions in the 18th – 19th centuries was analyzed. The role of their findings for the study of modern Kazakhstan was defined. The paper is very important for understanding the development of the relations between Kazakhstan and Russia in the sphere of scientific research. German researchers played an important role in development of the theoretical basis of Russian science and were politically active in the farthest regions of the Russian Empire, i.e., often finding themselves in extremely risky conditions. Participation of foreign specialists strengthened the relations between various scientific schools, which was crucial for Russian science of that time. The results of joint studies were published in Western European countries, thereby initiating the discussion among foreign scholars. These studies enabled the development of methodology, as well as the mutual enriching in various scientific areas. However, data on some field materials from these expeditions remain unpublished in the CIS and, thus, unfamiliar to professional historians, but they are of particular importance to modern researchers of the history and historical geography of Kazakhstan during the pre-revolutionary period.